Cancer cell membrane-coated biomimetic platform for tumor targeted photodynamic therapy and hypoxia-amplified bioreductive therapy. (October 2017) - Li, Shi-Ying; Cheng, Hong; Qiu, Wen-Xiu; Zhang, Lu; Wan, Shuang-Shuang; Zeng, Jing-Yue; Zhang, Xian-Zheng
Abstract: Modulating tumor microenvironment to amplify the therapeutic efficiency would be a novel strategy for effective cancer treatment. In this work, based on the TPZ-loaded porphyrinic metal organic framework PCN-224 (PCN stands for porous coordination network), a cancer cell membrane-coated nanoplatform (TPZ@PCN@Mem) was fabricated for tumor targeted PDT and the successively resulting hypoxia-amplified bioreductive therapy. After administration, TPZ@PCN@Mem exhibited the selective accumulation and long-term retention at tumor tissue due to the immune escape and homologous targeting endowed by the cancer membrane coating. Upon light irradiation, PCN-224-mediated toxic reactive oxygen species (ROS) were generated for PDT, and the resulting local hypoxia microenvironment would further accelerate the activation of TPZ for enhanced chemotherapy in 4T1 orthotopic tumor. The cascade synergistic therapeutic effects of TPZ@PCN@Mem could significantly suppress the primary tumor growth, and also inhibit its distal metastasis with minimal side effects. The study indicated an overwhelming superiority of utilizing this bioinspired strategy for tumor targeted PDT and hypoxia-activated bioreductive therapy, which provided a new insight for precise and effective tumor treatment.